2021
DOI: 10.6018/eglobal.427171
|View full text |Cite
|
Sign up to set email alerts
|

Creencias sexistas y actitudes de violencia de género. Situación de estudiantes universitario del área de la salud. Cartagena - Colombia

Abstract: Introducción: La violencia contra la mujer es un problema que atenta contra la igualdad, el desarrollo y la paz social. Situación que se reconoce como factor asociado al deterioro en la calidad de vida de los individuos en la medida que se constituye en violación de los Derechos Humanos. Objetivo: Describir el grado de acuerdo o desacuerdo entre las creencias sexistas y las que conducen a la violencia en estudiantes del área de la salud de una Institución de Educación Superior de Cartagena. Materiales y método… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Si se amplía el ángulo de comparación con otros trabajos que han analizado el sexismo en universitarios de Colombia, por medio de otros instrumentos psicológicos; los datos que los autores hemos obtenido también serían coincidentes con estos cálculos. De este modo Saldarriaga et al (2021) identificaron que los estudiantes de enfermería de Cartagena de Indias son más machistas que las mujeres, al igual que los datos de sexismo ambivalente obtenidos por Cardona et al (2015) en Manizales. Llamativo el hecho que tanto varones como mujeres mantendrían creencias tales como que la mujer debería renunciar antes que el hombre a su carrera profesional para centrarse al cuidado del hogar en base a sus diferencias biológicas, siendo preocupante que los universitarios (mujeres incluidas) asuman creencias que favorecen la violencia de género (Cardona et al, 2015;Saldarriaga et al, 2021).…”
Section: Discusión De Resultados Y Conclusionesunclassified
“…Si se amplía el ángulo de comparación con otros trabajos que han analizado el sexismo en universitarios de Colombia, por medio de otros instrumentos psicológicos; los datos que los autores hemos obtenido también serían coincidentes con estos cálculos. De este modo Saldarriaga et al (2021) identificaron que los estudiantes de enfermería de Cartagena de Indias son más machistas que las mujeres, al igual que los datos de sexismo ambivalente obtenidos por Cardona et al (2015) en Manizales. Llamativo el hecho que tanto varones como mujeres mantendrían creencias tales como que la mujer debería renunciar antes que el hombre a su carrera profesional para centrarse al cuidado del hogar en base a sus diferencias biológicas, siendo preocupante que los universitarios (mujeres incluidas) asuman creencias que favorecen la violencia de género (Cardona et al, 2015;Saldarriaga et al, 2021).…”
Section: Discusión De Resultados Y Conclusionesunclassified
“…These rules of interaction between men and women remain in the cultural patterns of the majority population and are transmitted to children from a very early age through the stereotyped sexual models that are socialized (Caricote, 2006). Studies on the characteristics of gender roles in Colombia have been quite limited to the study of political violence in the country and in specific groups (Saldarriaga et al, 2021), and previous studies relating sexism and sexual behavior variables, such as condom use, were not identified in our review, so there are no results with which to contrast our findings.…”
Section: Discussionmentioning
confidence: 97%
“…Gender-based violence in universities is a frequent but little recognized fact, the lack of a culture of denunciation by those who are or have been victims of these situations, do not know where or with whom to go to denounce. Most of the students who suffer from gender violence are women and only some of them denounce it since there is a tendency to minimize the abuse considering that it is something unimportant, they are afraid, they lack information, there is mistrust in the authorities, they do not want their families to find out or because of shame; In addition, in many cases, there is a tendency to blame the victim and it is even accepted that violence is part of conflict resolution, which leads to the problem being minimized and the fault of the abuser being ignored [11]. Likewise, the subject is so little known that authorities and academic faculty do not give importance to the problem due to a lack of interest and inexperience in how to proceed in these cases, or because they are considered to be personal problems, a situation that it can favor the reproduction of gender violence inside and outside educational institutions.…”
Section: Introductionmentioning
confidence: 99%